STUDIES IN HELIODORUS - RICHARD HUNTER (CAMBRIDGE PHILOLOGICAL SO, 2020)
Nine essays on Heliodorus' Aithiopika, assessing narrative technique, the construction of culture and the work's reception by more recent cultures.
Keywords: Heliodorus, -- of Emesa -- Criticism and interpretation.; Heliodorus, -- of Emesa. -- Aethiopica.; Heliodorus, -- of Emesa; Aethiopica (Heliodorus, of Emesa); Romances, Byzantine -- History and criticism.; Roman courtois byzantin -- Histoire et critique.; Romances, Byzantine; Criticism, interpretation, etc.